Penyesuaian Diri Akademik Mahasiswa Ditinjau dari Regulasi Emosi dan Self-Esteem - Feny Mandoa; Habel Saud; Yansen Alberth Reba (Psychocentrum Review, 2021)
This study aims to analyze the effect of Emotional Regulation and Self-esteem on Academic Self-Adjustment. The method used is quantitative correlational. This research was conducted in the counseling study program in January-February 2021. The population of this study were students of the Guidance and Counseling Study Program at Cenderawasih University Class of 2016,2017,2018,2019 and 2020 with a total of 115 students. Based on the Slovin formula, 89 samples were obtained using the Proportionate Stratified technique. Random Sampling. The data collection technique used an emotional regulation questionnaire, a self-esteem questionnaire and an academic adjustment questionnaire with a Likert scale assessment. This study uses simple and multiple regression data analysis. The results of this study indicate that: there is an effect of emotional regulation on academic self-adjustment with the results of R2 = 38.9% and the effect of self-esteem on academic self-adjustment with the results of R2 = 62.6%. There is an effect of emotional regulation and self-esteem on academic self-adjustment, with the result of R2 = 69.3%, while the remaining 30.7% is influenced by other variables outside of this study.